The Relationship between Hip Waist Circumference Ratio and the Incidence of Coronary Artery Disease in the Cardiac Polyclinic of Public Health Hospital Tangerang District - Siti Ma’rifatun Jannah; Annisaa Fitrah Umara; Jaenudin Jaenudin (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2019)
Introduction: Coronary Artery Disease (CAD) leading cause of death in Indonesia. Central obesity is one of the risk factors that is often found in patients with CAD. The ratio of waist and hip circumference (waist hip ratio) method is considered as the anthropometric measurement which is more sensitive, cheaper and easier to assess central obesity. This study aims to determine the relationship between hip and waist circumference ratio with the incidence of coronary heart disease in cardiac polyclinic of Tangerang general hospital on 2018. Method: Study is an analytic study using cross-sectional study design. Sampling studied used consecutive sampling with 68 sampels.Analysis of relationship between hip and waist circumference ratio with the incidence of CAD uses statistic test of Chi Square with a significant degree (α) was 0,05.Results and Discussion: The result was old as much 43 56 – 65  years old (63,2%), gender as much 42 man (61,8%), Job as much 61 not work (89,7%), Based on the results with value of p-value was 0.004 (p value<α).Conclusion and suggestion: The conclution wasthe relationship between the ratio of waist and hips with the incidence of CAD. It recommends to add other variables for identfying incidence of Coronary Artery Disease. Keywords: Atherosclerosis, Coronary Artery Disease, Ratio Hip and waist